2015
DOI: 10.5430/jha.v4n5p18
|View full text |Cite
|
Sign up to set email alerts
|

How to design Lean interventions to enable impact, sustainability and effectiveness. A mixed-method study

Abstract: Objective: This study’s aim was to assess how various organisational designs affect Lean interventions’ success. Refinement of design and analytics contributes to the knowledge of organisational change management, and promote sound investment in quality improvement.Methods: A panel of 11 experienced Lean consultants ranked the success of 17 Lean interventions implemented at a university hospital. This was done by assessing their impact on outcome, the sustainability of the improved work processes and the effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…13,14 Nonetheless, most of the published lean studies have narrowed their focus to single technical applications or short-term improvements resulting in small pockets of best practices, with limited evidence on what drives effective system-wide lean implementation. 11,15,16 In order to understand the variation in how and when lean works in health care organizations, it is of a paramount importance to examine the organizational patterns that play a relevant role for the integration and the internalization of the change process. 10,16,17 A recent comprehensive review on the organizational factors that enable effective use of lean practices in health care has been conducted by the authors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…13,14 Nonetheless, most of the published lean studies have narrowed their focus to single technical applications or short-term improvements resulting in small pockets of best practices, with limited evidence on what drives effective system-wide lean implementation. 11,15,16 In order to understand the variation in how and when lean works in health care organizations, it is of a paramount importance to examine the organizational patterns that play a relevant role for the integration and the internalization of the change process. 10,16,17 A recent comprehensive review on the organizational factors that enable effective use of lean practices in health care has been conducted by the authors.…”
Section: Introductionmentioning
confidence: 99%
“…11,15,16 In order to understand the variation in how and when lean works in health care organizations, it is of a paramount importance to examine the organizational patterns that play a relevant role for the integration and the internalization of the change process. 10,16,17 A recent comprehensive review on the organizational factors that enable effective use of lean practices in health care has been conducted by the authors. 18 Findings showed that literature on lean in health care has mainly investigated single organizational factors (see Table 1), lacking insight on how these elements are influencing each other and how lean change management strategies can be developed across the organization as a whole.…”
Section: Introductionmentioning
confidence: 99%
“… 3 4 However, sustainability of results after the initial period of short-term gains has been proven difficult to achieve, 5 6 and there is only limited understanding of factors influencing variation in results across organisational settings. 5 7 Plausible explanations for some of the observed limitations can be found in the scope of the lean improvement efforts. The types of outcomes addressed have mainly focused on operational aspects of performance, while little attention has been paid to sociotechnical aspects, such as employees' health, well-being and creativity.…”
Section: Introductionmentioning
confidence: 99%
“…lean has organizational and structural implications. When health care organizations manage to implement lean across organizational boundaries, the gains can be large and results can be sustained in the long term [ 35 ]. However, the shift towards a process-oriented organization in health care has proven difficult in Sweden and internationally [ 25 , 26 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“… The “model of improvement” which links the Plan-Do-Study-Act (PDSA) cycle of iterative learning with three questions related to goal, measurement, and what to change [ 11 ]. Results Factors related to lean success: comprehensive project organization, employee and safety-staff representation, and top management attendance [ 35 ]. Factors related to QI success: leadership from top management, QI experience, organizational culture, and data infrastructure/information systems [ 10 ].…”
Section: Introductionmentioning
confidence: 99%